Asymmetric Duopoly in Space - what policies work? - André De Palma; Fay Dunkerley; Stef Proost (European Regional Science Association (ERSA), 2005)
In this paper we study the problem of a city that is surrounded by two shopping centres. The first has low transport costs but is easily congested (near city center, access by road). The second one has higher transport costs but is less prone to congested access (ample public transport capacity etc.). Each sub-centre attracts shoppers and employees by setting prices and wages that are sufficiently attractive. Competition is imperfect since the shopping centers are not located at the same point and because both jobs and products are imperfect substituted. Moreover, congestion induces additional distortions since it is not priced at marginal cost. The solution concept is Bertrand Nash (asymmetric duopoly game). This solution is typically characterised by excessive congestion, especially for the nearby sub-center, and by positive mark-up prices. We study the welfare effects of three stylised policies. The first policy entails the capacity extension of the road connecting the city center to sub-center 2. This policy will not necessarily lead to less congestion as more shoppers will be attracted by the lower transport costs. This result is reminiscent of the well known Braess paradox in transport economics. In our paper we add product differentiation and it will be the degree of product differentiation that will determine how successful the capacity extension policy is. The second policy envisaged entails the addition of congestion pricing (or parking pricing etc.) for the most congested sub-center. This will decrease its profit margin (see de Palma & Proost, forthcoming 2005) and will attract more shoppers. The third policy considers the addition of one (or several) more remote sub-centers. This is more like a subsidy type of policy that is more acceptable for politicians. This policy will again ease the congestion problem for the nearby sub-center, but such policies, which entail heavy investments, will be achieved at very high costs.
Keywords: 330